Análisis comparativo para la evaluación de motores de juegos en el desarrollo de juegos serios. - Tomalá González, Jennifer del Carmen (2019)
The present degree work aims to carry out a comparative analysis for the evaluation of Games Engines in the Development of Serious Games, allowing to determine strengths and weaknesses of two significant tools employed in the creation of serious games, in order to allow the developer to make a correct decision making when selecting the tool according to their needs. The research begins with the elaboration of a Systematic Literature Review (SLR) concerning Methodologies and Game Engines for the implementation of serious games, succeeding in confirming that, of the wide variety of game engines currently available, Unity and Unreal Engine are the most used in this type of development, because they offer great advantages as cost, learning curve, work flow acceleration, among others. On the basis of this, criteria proposed by several authors is determined and categorized when choosing this type of tool, which are framed in basic characteristics and components of the engine. So, we proceed to design a serious game prototype and then create it in each of the selected engines, which allows to analyze factors such as: functionality, usability, documentation, response times, and performance of the PC when using each of the engines. Finally, a comparative analysis of the characteristics, components and the experimental evaluation associated with the production of the serious game in the two game engines used in this study is carried out. Keywords: Development of serious games, game engines, Unity Engine, Unreal Engine.